Pendidikan Holistik sebagai Sintesis Multidisipliner yang Komprehensif bagi Pembentukan Manusia Masyarakat Bima - Muhammad Yamin; L. Virginayoga Hignasari; I Putu Sriartha; I Made Pageh (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine holistic education as a multidisciplinary approach with strong potential for human development within the Bima community. Holistic education is conceptualized as an educational paradigm that integrates cognitive, affective, psychomotor, moral, social, spiritual, and ecological dimensions in a balanced and interconnected manner. In the context of Bima society, this approach is particularly relevant because it aligns with local philosophical values such as Maja Labo Dahu and Ngaha Aina Ngoho, which emphasize integrity, ethical conduct, diligence, social responsibility, and environmental stewardship. The research employs a descriptive qualitative method through an extensive literature review and phenomenological analysis of educational practices in Bima. The findings indicate that holistic education functions as a multidisciplinary synthesis, drawing upon pedagogy, anthropology, developmental psychology, sociology, and ecopedagogy to support comprehensive human formation. The integration of local wisdom into educational processes has been shown to effectively strengthen character education and ecological awareness, enabling learners to develop competitiveness and global readiness without eroding their cultural identity. Furthermore, holistic education provides a strategic framework for responding to contemporary educational challenges, including moral degradation, environmental crises, and the fragmentation of knowledge. By positioning local culture as the core of educational integration, this approach fosters sustainable human development rooted in local values while remaining responsive to global demands. The study concludes that holistic education represents a viable and contextually grounded strategy for advancing sustainable human development in the Bima community in the era of globalization.